Reconsidering C.B. Macpherson : from possessive individualism to democratic theory and beyond - Hansen, Phillip, 1949- (University of Toronto Press, 2015)
"This manuscript seeks to provide a fresh and comprehensive re-interpretation of the ideas of the world-renowned Canadian Political theorist, C.B. Macpherson."--